Essays on the history of scientific thought in modern Japan - Kanamori, Osamu 1954-; Carr, Christopher (Translator); Sheftall, Mordecai G. (Japan library (Shuppan Bunka Sangy?o Shink?o Zaidan))
"This book covers the history of physics, chemistry, and pharmacology in modern Japan, focusing on the 1920s through the early 1960s. Led by the editor's introduction, 'A Portrait of the History of Scientific Thought,' readers will soon find themselves in the middle of a complex double narrative comprising both 'the telling of history' and 'the telling of the history of history.' In the end, readers will come to understand an intricate historical aspect, made possible through such a grand and meta-appreciation"--Back cover.